Effect of Location on Flood Mitigation Practices in Niger Delta: The Case of Forcados Basin - Tano Dumoyei Agusomu; Horsfall Digieneni Eli (Current Research on Geography, Earth Science and Environment Vol. 1, 2025)
Floods are natural disasters that have been affecting human lives since time immemorial. Space perception and locational decisions affect the adoption of flood hazard mitigation in vulnerable areas. In the Forcados Basin of the Niger Delta region, the floodplain dwellers’ choice of mitigation measures is a function of a complex process involving several variables. The aim of this study is to investigate the residents’ awareness and adoption of flood mitigation measures in the Forcados Basin of the Niger Delta region. The nature of data evaluated in this study includes the locational addresses of residences adopting flood recovery measures (financial assistance, health and shelter programmes); structural measures (protecting against flood and modifying flooding) and non-structural measures (emergency response and flood preparedness). These data sets were collected from purposively selected communities prone to flooding, such as Patani, Sagbama, Bomadi and Ekeremor. Four hundred respondents participated in the study. The spatial distributions of floodplain dwellers’ residences were investigated in terms of their proximity and exposure to the hazard vis-à-vis information on the adjustments made. About 95% of the respondents indicated a very high level of awareness of flooding and flooding mitigation in the area. On the adoption of flood hazards mitigation measures, it was observed that, besides engineering structures, little is known about non-structural measures in the Forcados Basin. Regarding the rate of adoption of flood mitigation measures, the adoption of evacuation and planning measures decreased with distance from the 100-year floodplain, while flood-proofing increased outside the designated flood zones. The residents in very vulnerable areas in the basin responded spontaneously and resolved to immediate evacuation in the face of flooding. The results of the study suggest that the adoption of flood mitigation measures require little planning and are highly related to location in the Forcados Basin.